2012
DOI: 10.1007/s00167-012-1957-y
|View full text |Cite
|
Sign up to set email alerts
|

Interference screws should be shorter than the hamstring tendon graft in the bone tunnel for best fixation

Abstract: Purpose Interference screw fixation of hamstring tendon grafts in bone has to overcome the challenges that tendons have a slippery surface and viscoelastically adapt under pressure. As the typical failure mode of the graft is to slip past the interference screw, it was hypothesized that the position and configuration of the graft end may be of influence on the fixation strength. Methods Different configurations of the graft ending and its effect to primary fixation with interference screws after viscoelastic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Even at the 0° traction angle, the maximum pullout load of the long-graft group was higher than that of short-graft group. Stalder et al 4 showed that better fixation strength is achieved if the tip of the IS does not extend past the end of the tendon graft, and they theorized that if the end of the tendon graft is caught at the tip of the IS, the fixation strength is affected. We believe that the pullout load difference for the 0° traction angle observed in the present study reflects this idea, although the difference in the contact area as described earlier is considerable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even at the 0° traction angle, the maximum pullout load of the long-graft group was higher than that of short-graft group. Stalder et al 4 showed that better fixation strength is achieved if the tip of the IS does not extend past the end of the tendon graft, and they theorized that if the end of the tendon graft is caught at the tip of the IS, the fixation strength is affected. We believe that the pullout load difference for the 0° traction angle observed in the present study reflects this idea, although the difference in the contact area as described earlier is considerable.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Regarding the length of the screw, it has been reported that the use of a longer screw resulted in higher maximum pullout loads. 8,9 On the other hand, Stalder et al 4 showed that the pullout strength is increased with a short IS because a short IS can be caught on the tendon graft edge when a tendon graft longer than the IS is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,17 A 7-mm cannulated drill was passed over the wire up to 30 mm in depth to accommodate the free ends of the tendon and preventing the 25 mm screw of going beyond the free end of the tendon in the tunnel to ensure better fixation. 19 Using a 2-mm Beath pin, the ends of the tendon were passed through the femoral tunnel, with the stems coming out through the lateral condyle. Applying traction to the stem, the graft was fixed with a 7 Â 25-mm titanium interference screw and, as in the preconized technique, the screw head was buried subcortically.…”
Section: Methodsmentioning
confidence: 99%